Psychopathological symptoms in volleyball coaches: An approximation of their relationships with coping strategies and psychological inflexibility - Arbinaga, F.; Díaz-Rodríguez, J.; Gutiérrez-Fernández, J.; Moreno-San-Pedro, E.; Díaz-Ceballos, I. (International Sport Coaching Journal, 2026)
Mental health in sports is a highly prevalent and significant issue, and coaches are no exception. This study examines how psychological inflexibility and coping strategies influence psychopathological symptoms in volleyball coaches. The sample includes 187 coaches (72.7% male) with a mean age of 42.7 years and an average coaching experience of 14.9 years. Psychopathological symptoms were assessed using the Symptom Assessment-45 Questionnaire, psychological inflexibility was measured with the Acceptance and Action Questionnaire, and coping strategies were evaluated through the Brief COPE-28 Inventory. The results show that neither the competitive category nor the level of coaching certification is associated with differences in the studied variables. Coaches with high levels of psychological inflexibility, compared with those with low levels, exhibit significantly higher scores in psychopathological symptoms ( p < .001) and across all nine subscales. Similarly, regarding coping strategies, they score higher in ineffective coping ( p < .001), avoidant style ( p < .001), and social style ( p = .034). Regression models reveal an explanatory capacity of 45.4% for psychopathological symptoms, with significant predictive contributions from psychological inflexibility (* = 0.416) and ineffective coping (* = 0.365). Effective coping strategies, however, do not show significant predictive value. As a conclusion, it can be said that coaches with higher psychological inflexibility are those who present greater psychopathological symptomatology and more ineffective coping strategies. An important aspect is that modifiable constructs have been analyzed therefore they are amenable to intervention.